Writing the Abstract in Biology: A Review - Cárcamo Morales, Benjamín (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Due to its key role in the diffusion of knowledge in the academy, the abstract has been studied regarding aspects such as its lexical-grammatical performance and rhetorical organization. However, the ordering of these findings has not been made from the disciplinary view of biology. The objective of this study is to contribute with information regarding the writing of the abstract in the discipline of biology; in particular, regarding the rhetorical organization of the discursive genre, the author’s positioning and the coherence relations. For this purpose, an articulation of the results of several empirical studies is presented. As a result of this bibliographic review, a synthesis of the characteristics of this genre in biology is presented, among which the mandatory moves of “method” and “product”, its frequent writing in the first-person plural and the use of subordinated clauses to express author ́s subjective evaluations. It is hoped that this synthesis will be a didactic contribution to disciplinary literacy